An Analysis the Vocational High School Students’ Problem in Answering TOEIC Reading and Listening Test - April Liya Wulan Dari; Fera Zasrianita (Jadila: Journal of Development and Innovation in Language and Literature Education, 2021)
Test of English for International Communication TOEIC is a test of English communication skills developed by The Educational Testing Service (ETS). Currently, the Ministry of Education and Culture, through the Directorate of Vocational High Schools (DSMK), has opened opportunities for SMK throughout Indonesia to obtain international certification assistance through the SMK English Challenge 2020 program or facilitation of English language proficiency certification exams with TOEIC. This study investigates the problems of SMKN 3 Seluma students in answering the TOEIC reading and listening test. The Aims of this study was to investigate out and provide solutions related to students’ problem in answering TOEIC reading and listening test. To analyze these problems, this study used descriptive qualitative approach and interview as a data collecting technique. The results of this study indicate that there were two factors that become students’ problem in answering TOEIC reading and listening test, namely internal and external factors. Internal factors occur in students themselves where students did not understand the questions, vocabulary, or material being tested. While external factors occur beyond the ability of students, such as the facilities needed by students to take the test are still minimal. A good solution to overcome this problem is to prepare everything needed to take the TOEIC test in the form of learning resources, teaching staff, learning facilities and the most important is the mentality of the students who will take the test.